Epidermal growth factor receptor inhibitors in non-small cell lung cancer: current status and future perspectives - Zükin,Mauro (2012)
Two classes of epidermal growth factor receptor (EGFR) inhibitors are currently available for clinical use: tyrosine-kinase inhibitors (TKIs) and monoclonal antibodies. The introduction of pharmacological agents that are able to inhibit EGFR represents an important step in the management of patients with advanced non-small cell lung cancer (NSCLC), the leading cause of cancer death worldwide. The use of EGFR inhibitors has not only led to meaningful therapeutic gains for patients, but has also expanded our knowledge about the disease itself, as it is now recognized that activating mutations of EGFR play a pathogenetic role in NSCLC, especially in adenocarcinoma, patients who never smoked or former light smokers, females, and Asian individuals. Patients with NSCLC and one or more of these features are more likely to harbor tumors with EGFR mutations, and hence to respond to TKIs, than individuals without these features. Currently, TKIs are considered by many as the treatment of first choice in both the first- and second-line treatment of patients with clinical or molecular predictors of therapeutic benefit, and chemotherapy is a second option in these cases, especially when activating mutations of EGFR are present. Moreover, TKIs and anti-EGFR antibodies may be used in other settings, and their therapeutic role in NSCLC is clearly expanding. However, despite an initially successful treatment course, patients with advanced NSCLC eventually develop resistance to TKIs; and novel agents that hold promise for the future include irreversible EGFR inhibitors with activity against resistance-conferring EGFR mutations.